2015
DOI: 10.1186/s40659-015-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

miR-205 promotes proliferation and invasion of laryngeal squamous cell carcinoma by suppressing CDK2AP1 expression

Abstract: BackgroundThe aberrant expression of microRNAs (miRNAs) has been found in various types of cancer. miR-205 was reported to be upregulated in laryngeal squamous cell carcinoma (LSCC) tissues, however, the mechanisms by which miR-205 functions as a regulator of LSCC are largely unknown.ResultsIn this study, Real-time qPCR and Western blot assay showed that expression of miR-205 was upregulated and expression of cyclin-dependent kinase 2-associated protein 1 (CDK2AP1) was downregulated in LSCC tissues. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…Previous studies have demonstrated that miR-205 functions as an oncogene in numerous types of human cancer (20)(21)(22). For example, in laryngeal squamous cell carcinoma, miR-205 was upregulated and enhanced cell growth and invasion via negative regulation of CDK2AP1 expression level (20). Expression levels of miR-205 were reported to be increased in endometrial cancer tissues (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-205 functions as an oncogene in numerous types of human cancer (20)(21)(22). For example, in laryngeal squamous cell carcinoma, miR-205 was upregulated and enhanced cell growth and invasion via negative regulation of CDK2AP1 expression level (20). Expression levels of miR-205 were reported to be increased in endometrial cancer tissues (21).…”
Section: Discussionmentioning
confidence: 99%
“…A number of target genes of miR-205 have been previously identified, including zinc finger E-box binding homeobox 1 (27) in gastric cancer, tumor protein p53 inducible nuclear protein 1 in prostate cancer (31), transforming growth factor-α in osteosarcoma (20), cyclic AMP responsive element binding protein 1 in colorectal cancer (32), cyclin dependent kinase 1 associated protein 1 in laryngeal squamous cell carcinoma (23) and angiomotin in breast cancer (30). However, no target of miR-205 has been identified in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-613 reduces LSCC cell proliferation, invasion, and blocks G1/S phase transition by targeting the PDK1 gene [13]. Furthermore, miR-1297, miR-143-3p, miR-503 and miR-205 also promote LSCC cell progression [14][15][16][17]. Recent studies have confirmed that miR-17-5p plays critical roles in tumor progression, such as pancreatic cancer, breast cancer, hepatocellular carcinoma, gastric cancer and prostate cancer [18][19][20][21][22].…”
mentioning
confidence: 97%